Multiple Nodules Arising within a Birthmark on the Scalp: A Quiz - Takuya Mizukami; Yasuyuki Fujita; Yuka Maya; Kunihiro Kawashima; Takahiro Tsuji; Eiichi Arai; Koichi Honma; Satoko Shimizu (Acta Dermato-Venereologica, 2020)

(untitled)
Abstract is missing (Quiz)